Pengaruh Pendidikan Kewirausahaan Terhadap Minat Berwirausaha pada Mahasiswa Pariwisata Universitas Kepanjen - Ainul Mufarichah; Bagus Pramudia Ananta; Surya Angara Putra (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
Entrepreneurship education is an important strategy for fostering students’ entrepreneurial intentions, particularly in the tourism sector, which has significant potential to support regional economic development. Malang Regency, as an area with diverse tourism destinations, requires tourism human resources who are not only academically competent but also possess strong entrepreneurial mindsets. This study aims to analyze the effect of entrepreneurship education on the entrepreneurial intention of students in the Tourism Study Program at Universitas Kepanjen. The research employed a quantitative approach with a survey design. Data were collected through structured questionnaires distributed to 52 tourism students who had completed entrepreneurship courses. Data analysis was conducted using simple linear regression with the assistance of SPSS software. The results indicate that entrepreneurship education has a positive and significant effect on students’ entrepreneurial intention, with a significance value of less than 0.05 and a coefficient of determination of 38.8 percent. These findings suggest that improving the quality of entrepreneurship education can enhance tourism students’ intention to establish independent businesses in the tourism and creative economy sectors, thereby contributing to the strengthening and sustainability of tourism development in Malang Regency